Co-fermented yellow wine lees by Bacillus subtilis and Enterococcus faecium regulates growth performance and gut microbiota in finishing pigs - Zhang, Yu; Wang, Cheng; Su, Weifa; Jiang, Zipeng; He, Huan; Gong, Tao; Kai, Lixia; Xu, Huangen; Wang, Yizhen; Lu, Zeqing (Frontiers in Microbiology, 2022)
Fermented yellow wine lees (FYWL) are widely used to increase feed utilization and improve pig performance. Based on the preparation of co-FYWL using Bacillus subtilis and Enterococcus faecalis, the purpose of this study was to investigate the effects of co-FYWL on growth performance, gut microbiota, meat quality, and immune status of finishing pigs. 75 pigs were randomized to 3 treatments (5 replicates/treatment), basal diet (Control), a basal diet supplemented with 4%FYWL, and a basal diet supplemented with 8%FYWL, for 50 days each. Results showed that the 8% FYWL group significantly reduced the F/G and increased the average daily weight gain of pigs compared to the control group. In addition, 8% FYWL improved the richness of Lactobacillus and B. subtilis in the gut, which correlated with growth performance, serum immune parameters, and meat quality. Furthermore, acetate and butyrate in the feces were improved in the FYWL group. Simultaneously, FYWL improved the volatile flavor substances of meat, increased the content of flavor amino acids, and played a positive role in the palatability of meat. In addition, FYWL increased serum IgA, IgM, IL-4 and IL-10 levels. Overall, the growth performance, the gut microbiota associated with fiber degradation, meat quality, and immune status were improved in the 8% FYWL group.